Functional Characterization and Categorization of Missense Mutations that Cause Methylmalonyl‐CoA Mutase (MUT) Deficiency. Issue 12 (December 2014) - Forny, Patrick; Froese, D. Sean; Suormala, Terttu; Yue, Wyatt W.; Baumgartner, Matthias R.
ABSTRACT Methylmalonyl‐CoA mutase (MUT) is an essential enzyme in propionate catabolism that requires adenosylcobalamin as a cofactor. Almost 250 inherited mutations in the MUT gene are known to cause the devastating disorder methylmalonic aciduria; however, the mechanism of dysfunction of these mutations, more than half of which are missense changes, has not been thoroughly investigated. Here, we examined 23 patient missense mutations covering a spectrum of exonic/structural regions, clinical phenotypes, and ethnic populations in order to determine their influence on protein stability, using two recombinant expression systems and a thermostability assay, and enzymatic function by measuring MUT activity and affinity for its cofactor and substrate. Our data stratify MUT missense mutations into categories of biochemical defects, including (1) reduced protein level due to misfolding, (2) increased thermolability, (3) impaired enzyme activity, and (4) reduced cofactor response in substrate turnover. We further demonstrate the stabilization of wild‐type and thermolabile mutants by chemical chaperones in vitro and in bacterial cells. This in‐depth mutation study illustrates the tools available for MUT enzyme characterization, guides future categorization of further missense mutations, and supports the development of alternative, chaperone‐based therapy for patients not responding to current treatment.